Cross-Institutional Digitalisation and the Digi-Service Bubble Pitfalls in Public Sector Transformation in Indonesia - Ondy Asep Saputra; Arif Nugroho; Duratul Ain Tholibon; Rudi Salam (Journal of Contemporary Governance and Public Policy, 2025)
Digitalisation has emerged as a dominant trend in public service delivery, often regarded as a means to reduce costs, improve accessibility and contribute to Sustainable Development Goal (SDG) 9 on Industry, Innovation and Infrastructure. However, as institutions adopt digital service models, critical questions remain regarding the urgency, effectiveness and potential shortcomings of such reforms. This study examines Indonesia’s public sector amid a wave of digital reforms, exploring the broader implications of cross-institutional digitalisation through the concept of the digi-service bubble. This refers to a condition where the pace of digital adoption exceeds the capacity for strategic planning and meaningful implementation. Data were collected via online surveys involving 50 participants, complemented by in-depth interviews with 20 informants. The research investigates public perceptions of digital services, particularly in relation to their necessity, accessibility and practical effects on everyday governance interactions. The findings highlight three key patterns. First, there is broad consensus on the importance of digitalisation. Second, perceptions vary based on educational background. Third, fragmented digital infrastructure remains a challenge, leading to redundancy and inefficient resource allocation. While digital transformation in public services is broadly supported, long-term success depends on strategic coordination, inclusivity and coherent policymaking. The study underscores the need for integrated digital infrastructure, widespread digital literacy and transparency in governance. These factors are vital to avoiding inefficient or poorly implemented digital initiatives, which typify the digi-service bubble.